Kesan modul pendidikan kesihatan dalam meningkatkan kepuasan hidup kalangan perawat keluarga yang merawat pesakit strok kali pertama di rumah - Hussain, Noor Aini (2016)
The involvement of family member as “unpaid caregivers” negatively affected the caregivers’ psychological, physical and social health either while the stroke survivors are in hospitals or at home. The objective of this study was to determine the effect of the health education module on life satisfaction among family caregivers of first ever stroke survivors at home, health progress of first ever stroke patient and predictors of life satisfaction among family caregiver. A quasi-experimental pre and post intervention design with purposive sampling was used in this study. Life satisfaction of family caregivers was measured using the Bakas Caregiving Outcome Scale (BCOS), whereas the health status perception of stroke patients was measured by Barthel’s Index (BI) and EQ-5D. A repeated measures Split Plot two-way ANOVA and multiple linear regression test was used to test the hypothesis. The assumption of SPANOVA test was met when the Levene’s and Box test are not significant (p > .05). Huynh-Feldt Epsilon value was used when Mauchly Sphericity test is significant [p < .05]. This research involved 52 family caregivers of intervention group, while 50 family caregivers were in the non intervention group of hospitalized first ever stroke patients from two tertiary hospitals in Kelantan. Data collection was atpreintervention visit (hospital) and post intervention home visits (1 month, 3 month and 6 month). The findings showed that majority of the family caregivers are among the aged of 20 to 60 years old, female, unemployed and wife or children of the first-ever stroke patient. The SPANOVA findings showed that there was a significant interaction between repeated measure time and family caregiver groups [F (2.45, 245.73) = 25.76, p < .001, η2 = .21] and main effect between the groups of family caregivers [F (1, 100) = 65.980, p < .001, η2 = .39] on the family caregivers life satisfaction score. The findings also showed that there was a significant interaction between repeated measure time and first ever stroke patient groups [F (2.09, 209.58) = 9.29, p < .000, η2 = .85] and main effect between groups of first ever stroke patient [F (1, 100) = 23.20, p < .000, η2= .19] on the score of health perception status of stroke patient. A large effect size was evident. Significant predictors of life satisfaction of family caregivers were combination of caregiver’s health and presence of chronic diseases [F (2, 49) = 34.807, p < .001], stroke patient’s age (> 61 years) [F (1, 50) = 9.436, p <. 05] and physical function ability [F (1, 50) = 9.363, p < .05]. Families are responsible for their disabled sick family members in hospital or at home because of the social values and religion. A structured health educational module with skills manual developed in this study has proven to improve life satisfaction of the family caregivers and health status perception of the first-ever stroke patients. This health educational module is suggested to be a guidance for nurses and become a tool in the improvement of existing health education modules for the benefit of the family caregivers, stroke patients, and rehabilitation centers.